The forestry system and the timber market in China - Zou, Pan (University of Ottawa (Canada), 2004)
In the past two decades, China has achieved a spectacular success in its economic growth. As a basic input for the production process, the forest resource has been one of the fundamental factors propping up the expansion of China's economy. When China is absorbing imports of timber products in the global market, studies of China's forestry system and its timber market incite greater interest. This paper represents a systematic approach to probe into the comprehensive realities of China's forestry system and its timber market. Econometric methods are applied in analyzing the demand and supply patterns. The empirical analysis is used to forecast the quantity demanded for timber products in China.
Keywords: Agriculture, Forestry and Wildlife.; Agriculture, Wood Technology.; Engineering, System Science.